2022
DOI: 10.3390/jcm11226873
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes following Common Femoral Endarterectomy

Abstract: Thromboendarterectomy of the common femoral artery (CFA) for occlusive disease is a crucial procedure in vascular surgery. As an outcome reference for emerging endovascular procedures and new devices, we need more robust evidence of the outcome of this gold standard technique. The purpose of this study was to report 10-year results after femoral endarterectomy (FEA). A retrospective review of medical records at our institution identified eighty consecutive patients (91 limbs) who underwent FEA for CFA lesions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…For this patient, it was felt to be appropriate given the unusual circumstances. Several studies demonstrate good long-term outcomes for femoral/popliteal endarterectomy, a common vascular procedure used for patients with claudication and critical limb ischaemia 2–4. Hashimoto et al demonstrated that at 5, 10 and 15 years following isolated endarterectomy, no further revascularisation procedures on the side initially operated on were required in 68%, 50.6% and 42.5% of cases, respectively 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this patient, it was felt to be appropriate given the unusual circumstances. Several studies demonstrate good long-term outcomes for femoral/popliteal endarterectomy, a common vascular procedure used for patients with claudication and critical limb ischaemia 2–4. Hashimoto et al demonstrated that at 5, 10 and 15 years following isolated endarterectomy, no further revascularisation procedures on the side initially operated on were required in 68%, 50.6% and 42.5% of cases, respectively 3.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrate good long-term outcomes for femoral/popliteal endarterectomy, a common vascular procedure used for patients with claudication and critical limb ischaemia 2–4. Hashimoto et al demonstrated that at 5, 10 and 15 years following isolated endarterectomy, no further revascularisation procedures on the side initially operated on were required in 68%, 50.6% and 42.5% of cases, respectively 3. Thus, endarterectomy has been seen to be a beneficial procedure which has a high success in a range of patients, so the use of graft endarterectomy in selected vascular patients may prove useful.…”
Section: Discussionmentioning
confidence: 99%
“…Upon closer inspection, OSR may not be as innocuous as originally believed, with postoperative complications delineated in up to one-quarter of treated patients. Research has been limited to registries and a small number of trials, which have not indicated a decrease in periprocedural complication rates over the past decades [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. The most frequent complications are still related to the incision site and include wound complications owing to infection, dehiscence, lymphatic leakages, haematoma, and neural dysaesthesia [ 9 , 12 , 13 ].…”
Section: Narrative Reviewmentioning
confidence: 99%
“…1) [1]. Die langfristigen Offenheitsraten für solche lokalen Rekonstruktionen sind mit einer Offenheitsrate von 98 % nach 3 Jahren sehr gut [2,3]. Bei vorliegendem kollateralisiertem Verschluss der A. femoralis superficialis, in Kombination mit einer relevanten Abgangsstenose der A. profunda femoris, kann schon die alleinige Rekonstruktion der Femoralisgabel unter Einbeziehung des proximalen Anteils der A. profunda femoris durch eine sog.…”
Section: Die Chirurgische Rekonstruktion Der Femoralisbifurkationunclassified